STRATEGY DEVELOPMENT OF SALES ORGANIZATION USING FUZZY AHP: DIGITAL TRANSFORMATION OF FMCG - Kusuma, Adhitya Rendra; Syarief, Rizal; Ekananta, Arry; Sukmawati, Anggraini (Universitas Brawijaya, Indonesia, 2023)
A clear understanding of internal strength allows the company to innovate and adapt in a highly competitive Fast-moving consumer goods market. Therefore, the company's ability to oversee risk and opportunities determines the company's resilience. By employing homogeneous purposive sampling, which focused on the member population of 11 FMCG companies, the present study processed quantitative data from a questionnaire using a Likert scale and qualitative data through in-depth interviews with stakeholders. The data was collected through one-on-one in-depth interviews with 11 respondents online and offline in 12 major cities from August to November 2022. Later, questionnaires were processed using AHP Fuzzy to explain and take into account the role of decision-makers resembling FMCG leaders by defining interactive factors, actors, objectives, and strategies. Factor-actor analysis found that the sales director was the actor with the most influential role in the leadership factor, the sales manager was influential in the Organizational Citizenship Behavior factor, and the sales director was a prominent actor in sales management control. The main goal of the president director, IT/Digital director, supply chain director, and sales director in digital transformation is increasing effectiveness/efficiency in business processes. Besides, the sales manager and sales supervisor aspire to achieve sales targets or sales growth set by the company. In increasing effectiveness/efficiency and achieving sales targets/sales growth set by the company, prioritized strategy can be done through the development of leadership, capability, and human resource capacity. Besides, customer/business partner-oriented digitalization is vital for increasing customer/business partner satisfaction with the company's services/business processes. Furthermore, the present study found leadership models as critical for digital transformation with the realistic scenario (iterative improvement) in all likelihood. Sales organizations are expected to consistently and continuously conduct experiments to find new ways of working and produce digital initiatives that companies need to answer customer/consumer demands. Those strategies can be done by clearly identifying factors, actors, objectives, and strategies for better business execution in digital transformation.